Induced humoral immunity of different types of vaccines against most common variants of SARS-CoV-2 in Egypt prior to Omicron outbreak. Issue 32 (30th July 2022) - El-Shesheny, Rabeh; El Taweel, Ahmed; Gomaa, Mokhtar R.; Roshdy, Wael H.; Kandeil, Ahmed; Webby, Richard J.; Kayali, Ghazi; Ali, Mohamed A.
Abstract: The diversity of SARS-CoV-2 continues to lead to the emergence of new SARS-CoV-2 variants. SARS-CoV-2 antibody assays are crucial in managing the COVID-19 pandemic by determining the neutralizing antibody response. This study aims to investigate vaccine-induced antibodies against most common variants of SARS-CoV-2 in Egypt. Sera samples were collected from vaccinated participants and neutralizing activity against the SARS-CoV-2 variants was determined using microneutralization assay. Our results show that the BNT162b2 (Pfizer-BioNTech), ChAdOx1 nCov-19 (AstraZeneca), and Ad26.COV2.S COVID-19 (Janssen) vaccines elicited neutralizing antibody responses more than the BBIBP-CorV vaccine (Sinopharm) against B.1, C.36.3, and AY.32 (Delta) variants. While vaccines remain highly effective in managing the COVID-19 pandemic, ongoing monitoring of vaccine effectiveness is needed.